Badash Is Our Ancient Spiritual Treasure - Nargiza Rahmatullaeva (Genius Journals, 2024)
In the article, it was scientifically substantiated that there was a unique musical direction known as "Badash" in the land of Surkhan, and that it occupies an important place in the national music art as a unique example of folk art